Distance Adult Learner Doctoral StudentsCreating a Nontraditional Doctoral Enclave - Royce Ann Collins (Adult Education Research Conference, 2015)
This paper explores a new model development for nontraditional adult learner doctoral enclaves. This specific enclave facilitates the movement from doctoral student to candidate to completion of the dissertation for adult learners who are employed fulltime and geographically located a distance away from the traditional support structures.
Keywords: nontraditional doctoral student; enclave